Evaluasi Tiga Metode Preparasi RNA Total untuk Deteksi Turnip mosaic potyvirus dari Benih Brassica rappa dengan Reverse Transcription-Polymerase Chain Reaction - Jati Adiputra; Sri Hendrastuti Hidayat; Tri Asmira Damayanti (Jurnal Fitopatologi Indonesia, 2012)
Turnip mosaic virus (TuMV) is an important seedborne virus that infects vegetable crops, especially Brassicae group, in Indonesia. Reliable detection method having high accuracy is required to detect the virus from seeds in order to avoid disease incidence as early as possible. A study was conducted to evaluate three total RNA extraction methods from Brassica seeds for TuMV detection using reverse transcription- polymerase chain reaction. The samples used are Brassica rappa seeds and seedling germinated for 3, 5, and 7 days. Total RNA extraction methods evaluated consisted of Wylie method, Randles method, and commercial kit as comparation. Total RNA extracted using Wylie and Randles methods has high concentration but low level of purity, on the other hand total RNA obtained using commercial kit has low concentration but high level of purity. Detection of TuMV from seed was successfully carried out using Wylie and Randles methods, TuMV from 3 - day old seedlings was detected using all three methodes, TuMV from 5-day old seedlings was only detected using Randles method, whereas TuMV from 7-day old seedlings was not detected using all three methodes. Total RNA extraction method using Wylie and Randles methodes is recommended for detection of TuMV from caisin seed using RT-PCR technique. Key words: Brassica rappa seed, reverse transcription- polymerase chain reaction, Total RNA, Turnip mosaic potyvirus